DEPICTION OF COMMON ENEMIES IN RELIGIOUS SPEECH: THE ROLE OF THE RHETORIC OF IDENTIFICATION AND PURIFICATION IN INDONESIAN RELIGIOUS CONFLICTS - Peter Suwarno (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
The role of common enemies in speech on religious issues have contributed to religious tension, conflict and even violence in Indonesia. It will select the most representative and most frequently used key terms from religiously related speeches and other texts containing the portrayal of common enemies. Using Burke’s theories of identification, this paper will explain the important roles of common enemies in group unity and in achieving certain objectives.